Design and Stress Analysis of the Prototype Bapro-1 Car Chase - Effendi, Sairul; Friatinia, Della Dwi; Arnoldi, Dwi; Jaya, Rangga Danar (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
BAPRO-1 is a type of prototype vehicle made by the SMES (Sriwijaya Mechanical Engineering Squad) team. This car was made to be contested in the KMHE (Energy Saving Car Contest) event which has the aim of creating more effective motorized vehicles, both in terms of vehicle design, quality of components and so on which can improve fuel efficiency in these vehicles. This article shows the stress analysis of the BAPRO-1 vehicle chassis using the Autodesk Inventor application. The chassis tested uses aluminum 6061 and stainless-steel. The test is carried out with the assumption of a static load, namely when the car is stationary. The purpose of writing this article is to determine the value of safety, deflection, and the Von Misses number. This study uses the Autodesk Inventor software to create 3D images.